The development of strategic planning concept process model for small medium enterprise (SME) in the construction industry - Yahya, Mohd Yamani (2015)
Small Medium Enterprise (SME) construction organisations are facing very demanding and competitive environment in the construction industry. The demanding and competitiveness of the construction industry required SMEs to be continuously vigilant to current situation and plan to the future. Many of these organisations failed to respond to ever changes environment and some of them were forced to fold their business. These pressures began to force SMEs construction organisation to shift the current short term planning to more strategically planning method such as strategic planning. SME construction organisations should engage in strategic planning activities to enhance their chances of survival and success due to this concept forces organisation to learn and adapt to current environment. Despite high fatality and have only 60 percent of survival rate, many SME construction organisations are reluctant to embrace strategic planning. Therefore, the aim of the study was to develop strategic planning model for guiding SMEs in their future planning. Additionally, the objectives of this research were to identify and investigate the influencing factors and barriers that hinder strategic planning application in SME construction organisations. In satisfying this aim and objective, the research was undertaken in two distinct phases. In phase one, an exploratory study that utilised semi-structured interviews to examine ‘why’ and ‘how’ strategic planning is used in practice by SME construction contractors was undertaken. A total of 22 in-depth interviews were conducted with owners and managers. It was revealed that most firms adopted a myopic and informal approach to strategic planning, with the main barriers to its implementation were plan in owner’s mind, unrealistic, busy, and un-forecast industry. In phase two, the findings from the interviews, in conjunction with the literature, were used to develop series of questions, which were subsequently tested using questionnaire survey. The questionnaire survey gathered quantitative data from a total of 133 SMEs regarding strategic planning practices and the factors that influenced its application. A number of non-parametric statistical techniques were used to analyse the data, which included relative index and factor vii analysis. The influence factors were identified and ranked by using relative index method (RI). The analysis revealed that five (5) variables that were considered the primary influence factors to strategic planning were people, market, technology, project, and financial. In addition, four (4) barriers including managerial, organisational, planning, and industry issues can be obstacle to the effectiveness of the implementation process of strategic planning. Subsequently, the research developed a generic strategic planning model for SMEs and was validated externally by construction industry practitioners. The proposed model provides basic fundamental for the SMEs in the construction industry to engage strategic planning process to enhance their organisation performance.